Reconstructive Urology: A Comprehensive Review of Flap and Graft Techniques – A review article - Abedi, Amir Reza; Seifipoor, Muhammad (Archives of Men’s Health, 2025)
Introduction: Flap-based reconstruction plays a pivotal role in modern urologic surgery, especially in the management of complex urethral, genital, and perineal defects. Methods: This review provides an integrated analysis of flap types, their indications, surgical techniques, and clinical outcomes, with primary emphasis on regional and free flaps. Buccal mucosa grafts and inguinal flaps are discussed as complementary options, particularly in challenging or salvage cases. Results and Conclusion: A thorough understanding of tissue selection, flap design, and complication management is crucial for optimal functional and aesthetic results.